Colobreathe® for the Treatment of Cystic Fibrosis-Associated Pulmonary Infections. Issue 1 (December 2015) - Schwarz, Carsten
Abstract Introduction The aim of the present study was to conduct a review of major publications on the use of Colobreathe® [colistimethate sodium dry powder for inhalation (CDPI) via Turbospin® ] for the treatment of cystic fibrosis-associated pulmonary infections. Methods Data for this research were extracted from original articles and reviews obtained through a search of the MEDLINE, MEDLINE in-Process, EMBASE, Cochrane Library, CINAHL, Web of Science, Conference Proceedings Citation Index and BIOSIS Previews databases through July 2015, using the key words "Colobreathe, " "colistimethate sodium dry powder inhalation" and "cystic fibrosis." Published data on Colobreathe® from international congresses were also included. Results One clinical trial, the phase III FREEDOM study, found that the use of Colobreathe® inhalation of 125 mg twice daily via Turbospin® was non-inferior to inhaled tobramycin solution. Two reviews of colistimethate sodium focused on its use and its efficacy. The relevant outcomes observed included forced expiratory volume in 1 s (FEV1% predicted), tolerability, health-related quality of life (HRQL), ease of use of the inhalation device, and pharmacokinetics. The results showed no inferiority for CDPI compared to inhaled tobramycin solution. Most of the HRQL scores tended to be in favour of the dry powder intervention, although none of the differences were statistically significant, but good treatment satisfaction was measured. One study focused on cost. Five conference abstracts on CDPI reported good implementation in a "real world setting, " significant high lung deposition, and good compliance and tolerability data for patients who continued to inhale CDPI for 4 weeks. Conclusions Studies demonstrated no inferiority of CDPI to tobramycin inhalation solution (TIS) in FEV1% predicted, and reported a preference of patients for the dry powder inhalation of colistimethate sodium because it was well tolerated, easier to use, less inconvenient and associated with improved adherence.